2017
DOI: 10.1108/ijchm-09-2015-0470
|View full text |Cite
|
Sign up to set email alerts
|

Diversity management research in hospitality and tourism: past, present and future

Abstract: Purpose The purpose of this paper is to present a review of diversity management research published in hospitality and tourism-specific and business discipline-based journals. The study objectives include attempting to assess the progress of diversity management research in hospitality and tourism, identifying gaps between the general business diversity management literature and the hospitality and tourism literature and providing hospitality and tourism scholars with suggestions to advance knowledge in divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 62 publications
6
92
0
3
Order By: Relevance
“…The second area, 'generational research', identified by Kalargyrou and Costen (2017), remains fragmented, although talent management has been a topic of considerable interest to the tourism sector. Many reports, for example, Deery and Jago (2015), conclude there is a widespread shortage of skilled labour in the hospitality and tourism sector.…”
Section: Diversity Management Research In Tourism and Hospitalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The second area, 'generational research', identified by Kalargyrou and Costen (2017), remains fragmented, although talent management has been a topic of considerable interest to the tourism sector. Many reports, for example, Deery and Jago (2015), conclude there is a widespread shortage of skilled labour in the hospitality and tourism sector.…”
Section: Diversity Management Research In Tourism and Hospitalitymentioning
confidence: 99%
“…Policy at a local, national and trans-national level should give consideration to these areas in formulating policy for tourism, as a considered counter-weight to a predominant focus in tourism development on marketing, increased visitation, infrastructure and services (Baum 2018). Research increasingly shows that diversity targets are only achieved through affirmative actions and quotas (Kalargyrou and Costen 2017). Research should be policy-informing in this regard and provide the tools for governments to require organizations to report the gender, sexuality and ethnicity of employees, as well as how many have disabilities, including those on casualized work arrangements.…”
Section: Research Agenda At the Macro Levelmentioning
confidence: 99%
“…In the North-American, European and Asian context several researchers have pursued surveys on diversity recently [7], [8], [9], [10], mainly focusing on the human resource managerial point [2], establishing a model of diversity management [11], or preparing a review of DM literature and research and its perspectives [12]. Researchers often explore diversity from the employees` viewpoints and experiences [2], [13], [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even among similar disciplines, there is a difference between hospitality and tourism research compared to general business areas. For example, Kalargyrou and Costen (2017) found that despite twenty years of research on the subject of diversity management, hospitality and tourism field has not progressed as much as general business. The hospitality and tourism scholarship has focused on evaluating organizational diversity programs and related training to identify best practices for managing diversity.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the general management research investigated the degree to which the widely held business case for diversity is valid and how specific demographic groups navigate their work environments. Hospitality and tourism scholars will need to be more intentional and focused on critical areas (Kalargyrou and Costen, 2017). Similarly, Perea and Brady (2017) found disconnect between the business school research and the world of business practice.…”
Section: Introductionmentioning
confidence: 99%